Federalizm europejski początków integracji europejskiej i doby kryzysu gospodarczego - JASKULSKI, ADAM (Rocznik Integracji Europejskiej, 2012)
The purpose of this paper is to compare the federalist concepts at the onset of European integration processes after the Second World War and in the time of struggling with the economic crisis. The starting point for the analysis is to present the initial situation, which in both periods was referred to as the crisis of the nation-state. In the first case, the nation-state was found guilty of instigating two world wars, and in the other it was guilty of the collapse of the public finances of eurozone Member States. Whether at the turn of the 1940s or now, an effective way out of the crisis is sought in federalism.